ผลของการจัดการเรียนรู้กีฬาว่ายน้ำโดยใช้เกมการ์ดที่มีต่อทักษะการว่ายน้ำท่ากบและท่าผีเสื้อของนิสิตนักศึกษาระดับปริญญาบัณฑิต - นิธิพร เชาว์สกุลวิริยะ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
This research aimed to study the effect of swimming learning management using game card to breast and butterfly strokes of undergraduate students and to study the effect the average score breast and butterfly stroked regular learning management. The sample comprised 60 and equally divided into two group. The first group was the control group with 30 students and the seconds group was the experimental group with 30 students. This research was conducted for 8 weeks: one period a week for 120 minutes, The research instruments were 1) lesson plans using game card to breast and butterfly stokes 2) breast and butterfly skill assessment form. The instruments have been qualified and validated by 5 experts (IOC=1.00,IRR=0.99).  The data were analyzed by mean, standard deviation and t-test. The experimental group learning though using game card had average breast and butterfly stokes score after the experiment 10.73 ± 1.41,9.87 ± 1.74 respectively different with higher score than the control group regular learning management 7.90 ± 2.56,7.30 ± 3.01 respectively.(t = 5.30,4.50 respectively)